Environmental Law and Sustainable Development: Legal Approaches to Climate Change Mitigation - Aris Krisdiyanto; Luis Santos; Maria Clara Reyes (Rechtsnormen: Journal of Law, 2026)
Background. Climate change mitigation has become a central concern of environmental law, particularly within the broader framework of sustainable development. Despite the proliferation of international agreements and domestic climate legislation, inconsistencies remain in translating sustainability principles into enforceable mitigation obligations. Purpose. This study aims to analyze how environmental law operationalizes sustainable development in designing legal approaches to climate change mitigation and to evaluate the effectiveness of binding and non-binding regulatory mechanisms.   Method. The research employs a qualitative doctrinal method combined with comparative legal analysis of international instruments and selected national jurisdictions, supported by inferential assessment of emission trends and case-based judicial review. Results. The findings indicate that jurisdictions incorporating quantified emission targets, structured compliance mechanisms, and explicit sustainability principles into statutory frameworks demonstrate more consistent mitigation outcomes. Flexible policy-based approaches encourage participation but generate variable performance due to weaker enforceability. Conclusion. The study concludes that sustainable development functions most effectively as a legal standard when embedded in binding legislation supported by institutional accountability.